Max Plus Algebra and It’s Aplication: Model of Simple Production System - Nasrulyati, Tri Siwi (Majalah Ilmiah Matematika dan Statistika, 2017)
This paper discusses the basic understanding of max plus algebra and an example of its application will be given. Next will be discussed a simple production system model with three machines.